KATA-KATA KANSEI PADA PRODUK BERBASIS BUDAYA UNTUK PEMENUHAN KEBUTUHAN MASLOW - Ratih Setyaningrum, I.G. Bagus Budi Dharma, dan Heddy Shri Ahimsa-Putra (Jurnal Teknosains, 2014)
Cultural aspect is not a priority within a product design and development process in Indonesia. On the other hand,cross culture products have success in the global market. That product is included in each Maslow level. Culturalaspect in product design is applied with a semantics, such as kansei words. The purpose of the research is to identifyculture products and kansei words based on Maslow needs. The research stage begins with mapping cultureproducts based on Maslow needs and determining kansei words. The result of this research is a classification ofkansei words. It is used to guide product development. Product development based on Maslow needs is one strategyto attract consumers. Therefore, product development and diversification product had met the needs of Maslow